Right to bail: special emphasis on criminal offences in Malaysia / Maziah Yong - Yong, Maziah (Faculty of Law, 1986)
Bail is believed to have evolved from a practice which goes back to Pre-Norman England and its history could be traced from the beginning of the reign of Edward I. In those days, it was the sheriffs who had the power of arrest and bail and the administration of justice was in their hands. At that time arrest meant imprisonment until the sheriff was disposed to hold his tourn or in more serious offences, until the arrival of the justices which often took years. Due to the unsanitary conditions in the prisons many prisoners died. Any frequent escapes of the prisoners, the sheriffs were held responsible by having to pay heavy fines. The sheriff, as representative of the crown and principal administrator of criminal justice, often admitted persons to bail. This is so to avoid the costly and troublesome burden of being personally responsible for the prisoners. Apart from that the sheriff also found a pecuniary advantage which could be obtained in allowing bail. The sheriffs made release on bail a lucrative business because they were not within the direct control of any judicial authority.